2020
DOI: 10.1113/jp280256
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and morphological changes in inner hair cells and their efferent innervation in the ageing mouse cochlea

Abstract: Age-related hearing loss is a progressive hearing loss involving environmental and genetic factors, leading to a decrease in hearing sensitivity, threshold and speech discrimination. r We compared age-related changes in inner hair cells (IHCs) between four mouse strains with different levels of progressive hearing loss. r The surface area of apical coil IHCs (9-12 kHz cochlear region) decreases by about 30-40% with age. r The number of BK channels progressively decreases with age in the IHCs from most mouse st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 76 publications
2
52
0
Order By: Relevance
“…Recent studies of aged OHCs are consistent with the idea that OHCs undergo a period of dysfunction prior to OHC loss. In a study of aged OHCs from early onset and late onset ARHL mouse models, Jeng and colleagues suggested that age-related OHC dysfunction is not due to apoptosis (Jeng et al 2021). They primarily focused their studies on OHCs from the 9-12kHz region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies of aged OHCs are consistent with the idea that OHCs undergo a period of dysfunction prior to OHC loss. In a study of aged OHCs from early onset and late onset ARHL mouse models, Jeng and colleagues suggested that age-related OHC dysfunction is not due to apoptosis (Jeng et al 2021). They primarily focused their studies on OHCs from the 9-12kHz region.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of membrane voltage, they showed that these biophysical properties decreased similarly with age, being highest in the youngest animals. In addition to OHC loss, they found decreases in OHC size as indicated by decreases in membrane capacitance, OHC ribbons, and the mRNA expression of SIc26a5 and OCM (Jeng et al 2021). Most, if not all, of these features changed similarly, independent of the ARHL onset suggesting that they are general features of aging in OHCs, and not necessarily related to the OHC dysfunction observed in ARHL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An L-glutamic acid based intracellular solution was used as it preserves cellular ultrastructure and improves the stability of recordings (Kay, 1992). A similar solution has extensively been used for investigating the biophysical properties of mammalian cochlear hair cells (e.g Corns et al 2018;Jeng et al 2020a;2020b).…”
Section: Whole Cell Patch Clampmentioning
confidence: 99%
“…Ahl is a recessive single nucleotide mutation at 753 (G=>A) on the Cdh23 gene on mouse chromosome 10 (Noben-Trauth et al, 2003). Cdh23 encodes cadherin 23, a protein necessary for inner ear development and maintenance of the sensory hair cell structures, in particular the tip and lateral links of the stereocilia at the hair bundle (Siemens et al, 2004; Söllner et al, 2004; Kazmierczak et al, 2007; Michel et al, 2005; Lagziel et al, 2005), but growing anatomical evidence also suggests that synaptic rearrangements on sensory hair cells also contribute to auditory functional decline in C57BL/6J mice (Stamataki et al, 2006; Zachary and Fuchs, 2015; Jiang et al, 2015; Jeng et al, 2021). Surprisingly, aging C57BL/6J mice, although showing cochlear ribbon synapse degeneration and hearing loss, display increased acoustic startle reflex amplitudes (Ouagazzal et al, 2006; Ison and Allen, 2003; Ison et al, 2007) and a time increase in recovery from ABR short-term adaptation (Walton et al, 1995).…”
Section: Introductionmentioning
confidence: 99%